"I ain' mad now and I know taint no use to lie": honesty, anger, and emotional resistance in formerly enslaved women's 1930s' testimony. Issue 3 (2nd September 2021) - Wilson, Beth R.
ABSTRACT: This article argues that racialized and gendered emotional standards shaped formerly enslaved women's decisions surrounding speaking honestly about slavery during their interviews in the 1930s. Scholars have demonstrated that Jim Crow racial dynamics impacted on interviewees' decisions to speak openly, but few have considered the constraining impact of society's emotional standards. For the three women considered in this article, however, speaking candidly about their memories of slavery was intimately connected with expressing anger about these experiences. Before they gave detailed descriptions of their experiences, they had to consider the constraints white society placed on Black Americans' expressions of anger, alongside specific restrictions on Black women's anger when speaking about white violence. When these women made considered decisions to speak more honestly and transgress these emotional standards they, therefore, undertook a form of "emotional resistance" that must be recognized alongside the intellectual agency they displayed.